OP127 Sugar And Spice And All Things NICE - Managed Access Agreements. (2019) - Hall, Adam; Liu, Lok Wan; Macaulay, Richard; Walsh, Sean
Abstract : Introduction: The National Institute for Health and Care Excellence (NICE) has increasingly agreed to reimburse innovative products with high levels of uncertainty as part of managed access agreements (MAAs) while additional data are collected, through the new Cancer Drugs Fund (CDF) or highly specialized technology (HST) pathways. This research aimed to review the data collection stipulations of current MAAs. Methods: We reviewed all current MAAs entered into between NHS England and manufacturers as of 29 October 2018 and key data were extracted. Results: Twenty-two MAAs were identified (19 through the CDF; three through HST). All MAAs involved an observational data collection component. The source of observational data collection was existing NHS databases (19/22 MAAs: 86.5 percent), existing independent registries (one MAA: 4.5 percent [ataluren]); bespoke MAA registry maintained by manufacturer (1/22 MAA: 4.5 percent [asfotase alfa]), and registries developed as a part of regulatory approval and maintained by the manufacturer (1/22 MAA: 4.5 percent [elosulfase alfa]). Only eight MAAs (asfotase alfa, ataluren, elosulfase alfa, brentuximab vedotin, venetoclax, ibrutinib, daratumumab, and pembrolizumab) had observational data collection as the primary method of data collection. Additionally, 17/22 MAAs (77 percent; all from the CDF) also required ongoing data collection from clinical trials as a key component of the data collection arrangement. Conclusions: This research identified observational data collection as a requirement in all MAAs, which is primarily through existing registries (except ataluren, which required development of a bespoke registry), while ongoing trial data collection was limited to the CDF. The relatively low cost of using existing registries to fulfil data requirements, with the ability to achieve reimbursement whilst still collecting data from ongoing RCTs, make MAAs an attractive proposition for manufacturers. NICE reportedly plan to increase use of MAAs, with ongoing NICE consultation for changes in the appraisal process potentially allowing expansion to include all indications, which would mean increased opportunities to explore innovative MAAs to support access in the future.